Conceptions of design research : discursive phenomenography in undergraduate visual communication design research - Yeo, Jesvin Puay-Hwa (2021)
This article adopts discursive phenomenography as a viable qualitative approach to identify the different conceptions that visual communication undergraduate students have of design research. Phenomenographic method was described by Limberg (1999) as an exploration of the world’s phenomena through the different encounters and comprehensions of people and societies. The phenomenographic findings map four qualitatively different ways, namely, Conception A: Process-focused Experience; Conception B: Knowledge and Skills-focused Experience; Conception C: Socially-focused Experience and Conception D: Self Awareness-focused Experience. The research results established an early step in understanding one aspect of the collective conceptions of design research in visual communication design. The findings are of interest to design educators who seek to know more about design research in order to equip design students with the relevant skills contributing to the field of design.